[PP.19.06] HEMODYNAMIC PARAMETERS OF COMMON CAROTID ARTERY ARE ASSOCIATED WITH ATHEROSCLEROTIC CARDIOVASCULAR DISEASE AND CARDIAC FUNCTION. (September 2017) - Kim, G.; Lee, S.N.; Moon, D.; Kim, J.H.; Moon, K.W.; Yoo, K.D.; Kim, C.M.
Abstract : Objective: Patients with atherosclerotic cerebrovascular disease appear to have larger common carotid arterial diameters and lower carotid flow velocities compared to those without the disease. The index of arterial stiffness is strongly related to the extent of atherosclerosis and cardiovascular events. The objective of this study was to elucidate the association between morphologic or hemodynamic parameters of the carotid artery and the vascular hemodynamic parameters of patients according to the atherosclerotic cardiovascular disease (ASCVD). Design and method: From patients who underwent carotid ultrasonography and non-invasive, semi-automated, radial artery applanation tonometry (Omron HEM-9000AI) in the Department of Internal Medicine at St. Vincents Hospital from July 2011 to July 2016, 594 subjects (360 male, mean age, 63 ± 12 years) were enrolled in this study. Results: After multivariate analysis, central blood pressure (SBP2) (B = −0.861, 95% CI 0.758 to 0.977, p = 0.021), peak systolic velocity (PSV) (B = 1.020, 95% CI 1.001 to 1.040, p = 0.044) and end diastolic velocity (EDV) (B = 0.896, 95% CI 0.845 to 0.950, p < 0.0001) were found to be associated with ASCVD after adjusting for age, gender, body mass index, fasting plasma glucose, HbA1c, smoking, diabetes, hypertension and use of antihypertensive medication and lipid-lowering therapy. In addition, SBP2, PSV and EDV are significantly associated with left ventricular systolic function (EF) (Figure). And also, in multivariate analysis after adjusting for above same parameters, PSV and diameter were associated with systolic function. Figure. No caption available. Conclusions: Therefore, common carotid hemodynamic parameters, in addition carotid intima-media thickness and palaque, are associated with ASCVD.